2014
DOI: 10.1002/cncr.28975
|View full text |Cite
|
Sign up to set email alerts
|

Tracking viable circulating tumor cells (CTCs) in the peripheral blood of non–small cell lung cancer (NSCLC) patients undergoing definitive radiation therapy: Pilot study results

Abstract: Background Assays identifying circulating tumor cells (CTC) allow noninvasive and sequential monitoring of the status of primary or metastatic tumors, potentially yielding clinically useful information. However, the effect of radiation therapy (RT) on CTC in patients with non-small cell lung cancer (NSCLC) to our knowledge has not been previously explored. Methods We describe here results of a pilot study of 30 NSCLC patients undergoing RT, from whom peripheral blood samples were assayed for CTC via an assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 30 publications
5
70
0
Order By: Relevance
“…Using an adenoviral probe that detected the elevated telomerase activity present in almost all cancer cells but not in normal cells, the median number of CTCs was assayed in 30 patients with non-small cell lung carcinoma. 19 Median CTC counts declined from 9.1 CTCs/ml to 0.6 CTCs/ml post-radiation therapy. Even the type of surgery appears to have an impact on the number of CTCs.…”
Section: Discussionmentioning
confidence: 89%
“…Using an adenoviral probe that detected the elevated telomerase activity present in almost all cancer cells but not in normal cells, the median number of CTCs was assayed in 30 patients with non-small cell lung carcinoma. 19 Median CTC counts declined from 9.1 CTCs/ml to 0.6 CTCs/ml post-radiation therapy. Even the type of surgery appears to have an impact on the number of CTCs.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast, an increase in CTC numbers is indicative of failure to respond to therapy. Changes in CTC numbers were also examined in patients with localised NSCLC undergoing radiation treatment the change in CTC numbers post treatment was evaluated as a surrogate for disease response (171). Additional studies have investigated subsets of CTCs linked to the therapy used.…”
Section: Treatment Response and Mechanisms Of Resistancementioning
confidence: 99%
“…Several studies associate CTC number to OS and/or PFS of metastatic NSCLC patients (32,33,48,57), meanwhile others do not find these associations (70,71). Many small trials have also demonstrated the association between CTC count and therapy efficacy, comparing the count before and after therapy (38,(72)(73)(74), or during target therapy, in order to detect the onset of resistance mutations (50,54,62,66,75). Even though most data suggest the utility of CTCs as biomarkers for assessing prognosis and monitoring therapy response in NSCLC, these assays are still not used in routine clinical practice, mainly due to the lack of standardized procedures allowing reliable and reproducible results that could be compared among different cohorts of patients.…”
Section: The Long Road Towards Clinical Utilitymentioning
confidence: 99%